2020
DOI: 10.46451/ijts.2020.09.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the COVID-19 Pandemic on ESL Learners and TESOL Practitioners in the United States

Abstract: This study seeks to understand the effect of the COVID-19 pandemic on a group of university ESL learners and their teachers in the U.S. While some schools quickly closed to protect students and teachers, others transitioned to remote teaching and learning. In addition to challenges associated with moving instruction to an online format, many teachers and students have had to grapple with a variety of additional issues regarding health, employment, finances, and other concerns. With the aim of better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 14 publications
4
54
1
2
Order By: Relevance
“…Hence, the students have to adopt e-learning as it is considered a favourable method to continue the learning process. However, a study conducted by Hartshorn & McMurry (2020) found that ESL students expressed that having schoolwork was overwhelming and considered "the most difficult challenge during the pandemic" (p.147). The students reported that being unable to talk to teachers and had to be in front of the computer for many hours was difficult and tiring.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the students have to adopt e-learning as it is considered a favourable method to continue the learning process. However, a study conducted by Hartshorn & McMurry (2020) found that ESL students expressed that having schoolwork was overwhelming and considered "the most difficult challenge during the pandemic" (p.147). The students reported that being unable to talk to teachers and had to be in front of the computer for many hours was difficult and tiring.…”
Section: Discussionmentioning
confidence: 99%
“…Findings also show that some teachers applied active coping strategies rather than avoidance strategies while increased levels of stress and negative emotions necessitated avoidant coping strategies (MacIntyre et al, 2020). Emergency online learning of English increased defeatist emotions and brought out certain stressors for the teachers and students (Hartshorn & Mcmurry, 2020;Maican & Cocoradă, 2021). Due to this new and unfamiliar form of teaching during the pandemic, most teachers experienced worry and anxiety (Gao & Zhang, 2020).…”
Section: Findings Of the Third Research Question Based On The Attitudes And Motivations Of Teachers And Students Towards Emergency Onlinementioning
confidence: 99%
“…English language related studies during the Covid-19 process (between March 2020 and February 2021) (Aji et al, 2020;Allo, 2020;Almekhlafy, 2020;Andriivna et al, 2020;Ariyanti, 2020;Astuti & Solikhah, 2021;Atmojo & Nugroho, 2020;Bailey & Lee, 2020;Chiatoh & Chia, 2020;Dahmash, 2020;Davies et al, 2020;Destianingsih & Satria, 2020;Farrah & Al-Bakry, 2020;Fatima, 2020;Fitria, 2020;Forrester, 2020;Fuad et al, 2020;Fuentes Hernández et al, 2020;Gao & Zhang, 2020;Hadianti & Arisandi, 2020;Hafidz, 2020;Hakim, 2020;Hamid, 2020;Hartshorn & Mcmurry, 2020;Hazaea et al, 2021;Hodges et al, 2020b;Hopp & Thoma, 2020;Huang et al, 2021;Kamhi-Stein et al, 2020;Karakuzu et al, 2020;Karataş & Tuncer, 2020;Karim & Hasan, 2020;Kawinkoonlasate, 2020;Khafaga, 2021;Kholis, 2020;Krishan et al, 2020;Kusumawati, 2020;Li et al, 2020;Lie et al, 2020;Loo, 2020;…”
Section: Study Focus Authors Nmentioning
confidence: 99%
See 2 more Smart Citations